2013
DOI: 10.1111/ijfs.12266
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different drying methods on drying characteristics, colour, total phenolic content and antioxidant capacity of Goldenberry (Physalis peruviana L.)

Abstract: Summary In this study, the effects of convective, microwave and microwave–convective drying methods on the drying characteristics, colour, total phenolic content and antioxidant capacity of goldenberry fruits were investigated. To select the most appropriate thin‐layer drying model for drying treatments, nine mathematical drying models were fitted to the experimental data. Based on the statistical tests used for evaluation, the Midilli et al. and Wang and Singh models were considered the best models to describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 36 publications
(40 reference statements)
4
40
0
2
Order By: Relevance
“…It is observed that the entire drying process of the whole lemons took place in the falling rate period. In some (29) …”
Section: Drying Kineticsmentioning
confidence: 99%
“…It is observed that the entire drying process of the whole lemons took place in the falling rate period. In some (29) …”
Section: Drying Kineticsmentioning
confidence: 99%
“…Dietary intake of antioxidants from medicinal plants has been increasingly accepted as a strategy for maintaining a healthy life [3]. The fruit of Physalis peruviana L. are called as goldenberry, gooseberry, cape gooseberry all over the world [4,5]. In Turkey, this fruit is known as "altın çilek or güveyfeneri" [6].…”
Section: Introductionmentioning
confidence: 99%
“…The C-values were not significantly different among the samples. Izli et al [24] observed that the goldenberry after the MWD presented lower C and a* values compared with the fresh samples. The colour difference (ΔE) for all treatments did not show significant differences.…”
Section: Quality Of the Final Productmentioning
confidence: 99%